Fungal deterioration control in outdoor environments by nano-additivated waterborne paint - Gámez Espinosa, Erasmo Junior (2021)
Biodeterioration of facades in building constructions causes economic damage. Filamentous fungi by their presence cause aesthetic damage to structural materials. In addition, its invasive growth through hyphae generates physical deterioration and due to its nutrition and excretion, they release enzymes, acids and pigments that cause chemical deterioration.To control fungal deterioration, paint additives with nanostructured biocides can be applied on facades.In addition, it is important that the nanoadditive maintains its long-term antimicrobial activity to delay fungal deterioration.The aim of this research was to assess the antifungal activity of a waterborne paint additivated with ZnO nanoparticles (ZnONPs) after 4 years exposed to the outdoor environment.